2013
DOI: 10.1111/apa.12109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nursing care on temperature environment in preterm newborns nursed in closed convective incubators

Abstract: For VLBW neonates nursed in skin temperature servo-control incubators, the decrease in abdominal skin temperature during caregiving was correlated with the type of procedure, incubator opening modalities and procedure duration. These parameters should be considered to optimize the thermal management of VLBW neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…The routine nursing and medical procedures consisted of catheterisation, nappy changes and baths. . The study protocol was approved by the regional ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…The routine nursing and medical procedures consisted of catheterisation, nappy changes and baths. . The study protocol was approved by the regional ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the hygrometric stress ranged from 150.7 ± 54.1 to 275.7 ± 74.0 minutes per day. As previously described for thermal stress , the hygrometric stress was closely related to the frequency of the incubator opening, which was high for the first few days after birth . Likewise, the mean duration of RH overshoot ranged from 142.1 ± 38.6 to 332.3 ± 73.4 minute/day.…”
Section: Discussionmentioning
confidence: 99%
“…The probe was covered with a foam and foil reflector patch, to reduce the heat loss to zero. As previously described, the infant's body temperature was correlated with the core body temperature (8,11,12). The peripheral skin temperature was continuously recorded via a probe placed over the foot.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…AAP/ACOG standards suggest keeping the ambient room temperature between 22°C and 26°C with a relative humidity level of 30%-60%. 7 Because the body temperature of premature infants in one study was found to decrease by up to 1.08°C per hour for some care procedures due to the type of procedure, length of procedure, and opening of the incubator, 38 it is important to minimize exposure to cold ambient air and use auxiliary heat for long procedures. Thomas et al found that there was a seasonal interaction with NICU room temperature, with ambient room temperatures differing as much as 2°F across seasons.…”
Section: Environmental Temperaturementioning
confidence: 99%